ASPEK PEMERINTAHAN dan PERUBAHAN KOMPREHENSIF ERA DIGITAL - Sadu Wasistiono (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2019)
ABSTRACT Digital era has been change human aspect significantly. Changing one aspect of life is boost another aspect . I tried to analysis impact of changing five aspect (management, organization, leadership, industry, society) to government aspect. External environment of government is playing important role to push changing in governmental management, organization, and leadership. Ideally, development of one aspect changing significant and simultan with another aspect, but empirically development of one aspect sometime faster than another aspect. Government as the higher organization of the state must control development of all aspect to maintain equilibrium of the state and society. Key words : digital era, changing continually, changing in government aspect.